Innovations and challenges in the production of hard seltzers - Fernandes, Gabriel Oliveira; Silva, José Antônio da; Granjeiro, Paulo Afonso; Gonçalves, Daniel Bonoto (Seven Editora, 2024)
Hard seltzers, standing out in the global alcoholic beverage industry, are prized for their lightness, refreshing taste, and moderate alcohol content. Meeting the demand for healthier beverages, these low-calorie water- and cane sugar-based fermented beverages have gained popularity, especially with the growing concern for health and wellness. In the United States, following regulatory changes in 2016, the launch of the first hard seltzer marked the beginning of a new beverage category, with a notable increase in sales during the Covid-19 pandemic. Production involves a careful fermentation process, with an emphasis on choosing the sugar source and using specific yeasts, such as Saccharomyces cerevisiae, to ensure quality and flavor. Sensory challenges are overcome with the addition of ingredients to enhance the taste while maintaining the healthy profile. The vital role of yeasts and the need for proper nutrition are critical to the success of the fermentation process. Hard seltzers, combining health, taste and innovation, promise a dynamic future in the beverage industry. DOI:https://doi.org/10.56238/sevened2023.008-019